PRELIMINARY STUDY OF INSULIN DRY POWDER FORMULATION: CRITICAL PROCESS PARAMETERS ON SPRAY-FREEZE-DRYING AND CRITICAL MATERIAL ATTRIBUTES OF TREHALOSE AND INULIN AS STABILIZER - MUNTU, CYNTHIA MARISCA; SURINI, SILVIA; AVANTI, CHRISTINA; HAYUN (International Journal of Applied Pharmaceutics, 2021)
Objective: The aim of this study was to obtain recommendations about critical process parameters (CPP) and the optimal ratio of trehalose and inulin as critical material attributes (CMA) on insulin dry powder formulation with spray-freeze-drying (SFD) method. Methods: Inulin dry powder was formulated with the SFD method, which consisted of an atomization process and freeze-drying (FD). SFD processes were optimized in order to obtain dry powder and CPP was analyzed. All seven variations of formulas proceeded with physicochemical characterization to obtain the optimal formula. Results: In the early optimization, there was a slight time lag between the atomization process and FD; as a result, some of the powder coagulated and crystallized. Another critical parameter was that the FD process should not be interrupted for at least 50 h of FD. Dry powder proceeded with physicochemical characterization, a formula without inulin showed semicrystalline properties, while six formulas had amorphous properties due to its combination. All formulas had a spherulite shape and rough surface. Five formulas with the combination of trehalose and inulin obtained dry powders with a diameter range of 30-43 μm, moisture content below 3.5%, and high encapsulation efficiency (EE). Formula with the ratio of 1:1 (F4) showed optimal properties with moisture content and EE of 2.62% and 99.68%, respectively. Conclusion: This study concluded that there were two critical process parameters in the SFD method. There should be no delay in the SFD process and when the FD is in operation, it should not be interrupted until the powder is dry. The optimal ratio for trehalose and inulin was shown by F4 with ratio of 1:1.